"Dare to share!": Bikt, moderskap och motstånd i Den stora mammabikten (Sociologisk Forskning, 2015)
”Dare to share!”: Confession, motherhood and resistance in The great mother confessionThis article explore the meaning of confession in a commercial, secular event – The great mother confession (TGM). The event is understood as imbedded in a therapeutic culture where emotional disclosure, in the form of confessions, is a highly valued practice. In a web-based confession-blog that constitutes part of the TGM-concept, confessions serve to free mothers from supressing norms. The blog becomes an arena for a volatile community where burdening and ”forbidden” thoughts and emotions becomes generalised and disarmed, releasing mothers from guilt. When this function of the blog is questioned from a competing sub-discourse of the therapeutic, emphasising the disclosure of happiness, a struggle emerges over the authority to define the meanings of confession. TGM can be understood as having potential for serving as an arena for challenging norms, but even as norms are implicitly addressed the practice makes a halt at that point. Norms that are seemingly dissolved in responses to confessions are not questioned, only recognised, normalised and de-politicised.
Keywords: confession; motherhood; norms; resistance; therapeutic society